Dinâmica socioambiental do alto curso da bacia do Rio Una/PE - Santos, Eliane Alves dos (2013)
The appreciation of the environmental medium of an object as a watershed becomes an addition of great relevance to the social context, as through the analysis of its main features has been viewing practices efficient environmental management and sustainable development. The upper course of the river basin Una is a spatial unit of great relevance in the context of the environmental state of Pernambuco, as well as at the regional level, and therefore, his study of the various aspects of local reality is of fundamental importance, in that positive steps to bring society. In this perspective, the research aimed to analyze the dynamics of this spatial area covering environmental information mainly from 1990. To achieve this and other goals specific prioritized approach geosystemic, using different methodological procedures, highlighting the literature and cartography, and other secondary data sources, as well as data collection in the field. The results of this study show that anthropogenic interference in varying degrees on the upper course and the basin as a whole, marked over time configure various stages of its evolutionary process that started from the sixteenth century through the process of occupation until leaving marks the present structure of land concentrated and serious problems that reflect the social development of the population. In addition, other socio-environmental problems also stand out as the degradation of water quality of the main course of the basin by the lack of conservation of their use and treatment of solid waste and effluents from various sources. At most, it is therefore concluded that other problems observed in socioeconomic development stems from the misuse of natural resources and land management.